Analysis Analisis Sistem Antrian dengan Model M/M/C dalam Meningkatkan Efektivitas Kinerja Sistem - Ibrahim, Novita; K. Nasib, Salmun; Nuha, Agusyarif Rezka; Katili , Muh Rifai; Nurwan Nurwan; Wungguli , Djihad (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Study This aim For analyze system queue at the Population and Registration Service Civil ( Disdukcapil) Bone Bolango Regency as well as apply the M/M/C (Multi Channel Single Phase ) queuing model optimizing performance system and upgrade effectiveness service to public . Arrival data visitors and time service collected for 5 days through observation . Analysis results show system applied queue moment This is the model (M/M/4 ): (FIFO/∞/∞) with level arrival visitors Poisson distribution , time service distribute Exponential , 4 counters service , discipline first-come first-served (FCFS) queues , as well source arrival and capacity queue No limited . Size performance the system in existing conditions shows time wait for the average visitor in system amounting to 26.4 minutes and time Wait in queue amounting to 44.4 minutes . For optimizing performance , research recommend application of the model (M/M/7 ) : (FIFO/∞/∞) with add amount counter service into 7 counters . In this model , level utility system (ρ) is below 50 % ie about 41%, which is considered effective Because enter in range level utility low (5%-10%). Application of the queuing model with 7 counters projected can shorten time wait for the average visitor in system to 18.42 minutes and time Wait in queue to 18 minutes . Findings This expected can increase effectiveness service and satisfaction public to service Disdukcapil Bone Bolango Regency.